Approaches for loss of vigilance in vehicle automation: a meta-analytical study - Gonçalves, Rafael Cirino; Quaresma, Manuela; Rodrigues, Claudia Mont’Alvão (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2017)
The phenomenon of behavioral adaptation induced by continuous use of vehicular automation is a very intriguing subject for researchers in the field of Human-Automation Interaction. Some authors believe that better tailoring of system design to driver needs and to the task requirements can improve human performance and mitigate the process of loss of vigilance. Nevertheless, the literature on this subject is far from reaching a consensus, so that the causal or aggravating factors for such process are not yet fully known. Based on this issue, the goal of this study was to list the most prevalent factors in the literature for the loss of driver’s vigilance capabilities during the use of autonomous vehicles (HAVs - Highly Automated Vehicles). To achieve the proposed goal, a meta-analytical study was conducted from a systematic literature review, followed by statistical significance tests. The results reinforce the idea that elements for communication and control of attention stimuli directed to the driver are of paramount importance for the occurrence of the studied phenomenon, so, we suggest further deeper studies on particular HMI application for HAVs.